Busy. Please wait.

show password
Forgot Password?

Don't have an account?  Sign up 

Username is available taken
show password


Make sure to remember your password. If you forget it there is no way for StudyStack to send you a reset link. You would need to create a new account.
We do not share your email address with others. It is only used to allow you to reset your password. For details read our Privacy Policy and Terms of Service.

Already a StudyStack user? Log In

Reset Password
Enter the associated with your account, and we'll email you a link to reset your password.
Don't know
remaining cards
To flip the current card, click it or press the Spacebar key.  To move the current card to one of the three colored boxes, click on the box.  You may also press the UP ARROW key to move the card to the "Know" box, the DOWN ARROW key to move the card to the "Don't know" box, or the RIGHT ARROW key to move the card to the Remaining box.  You may also click on the card displayed in any of the three boxes to bring that card back to the center.

Pass complete!

"Know" box contains:
Time elapsed:
restart all cards
Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

  Normal Size     Small Size show me how

Module 15

Complex Numbers

Write the the square root of -9 in terms of i To write the square root of a negative number in terms of i, use the property that if a is a positive number then √-a = √-1 * √a =i√a. so using i we can write √ -9 = √ -1*9 = √-1 * √9= i*3 or 3i
Write with i notation √-4 √-4= √-1*4= √-1*√4= 2i
Write with i notation √-7 √-1*7 = √-1*√7 =i√7
Write with i notation -√8 -√8 = -√-1*8 = √-1* √4*2 = -i*2√2= -2i√2
Multiply √-9 and √-16 We must first write each number in the form of bi. √-9√-16= 3i*4i = 12i^2= 12(-1) = -12
Multiply √-6*√-2 √-6*√-2 = i√6(i√2)=i^2√12 = -1(2)√3= -2√3
Multiply √4*√-4 √4*√-4 = 2(√-1*√4)= 2(2i)= 4i
Divide √-32/√8 √-32/√8 = i√32/√8= i√4= 2i
Add the complex number (4+3i)+(-3+4i)write the sum in the form a + bi (4+3i)+(-3+4i) = (4-3)+(4+3)i = 1+7i
Subtract the complex number 7i-(1-i)write the difference in the form a+bi 7i-(1-i)=7i-1+i= -1 +(7+1)i = -1+8i
Multiply the complex number -6i* 2i write the product in the form a+bi -6i*2i= -12i^2 = -12(-1)= 12+0i
Multiply the complex number (3-i)^2 (3-i)^2 = (3-i)(3-i)= 3(3)-3(i)-3(i)+i^2= 9-6i+(-1)= 9-6i
Divide 5/2i Multiply the numerator and denominator by the conjugate of 2i. 2i = 0+2i so its conjugate is 0-2i or -2i. 5/2i= 5(-2i)/2i(-2i)= -10i/-4i^2= -10i/-4(-1)= -10i/4= -5i/2 or 0-(5/2)i
Created by: 100000116474596